Modeling Inflation in Georgia - Maliszewski, Wojciech (IMF Working Papers; Working Paper ;, 2003)
The paper explains the behavior of inflation in Georgia in the post-stabilization period. A long-run equation linking prices to money and the exchange rate, as well as a short-run, dynamic equation for inflation are estimated. The inflation equation is stable, points to a dominant role of the exchange rate in the behavior of inflation and shows a low persistence of inflation in Georgia. The equation explains well the behavior of inflation after the Russian crises, when inflation increased sharply but was quickly brought under control, as the National Bank of Georgia kept its monetary policy tight and the exchange rate stable.